Global citizens. (9th May 2019) - Porteous, Debbie; Morgan, Debra; Solomon, Jennifer; Platt, Alan; Allan, Jaden; Shao, Chun Hua (Joy); Conner, Tony
Abstract : Nurses and nursing students from the UK and overseas are learning in each other's countries